ERM Implementation and Non-Performing Loans Performance: Comparison between Islamic Bank and Conventional Bank - Kurnia Indah Sumunar; Dyah Ayu Anggraheni; Mutiara Kemala Ratu (Journal of Islamic Economics and Social Science (JIESS), 2020)
There are different characteristics between islamic banking and conventional banking that cause a variety of questions, including the implementation of ERM. This study focuses on the effect of ERM implementation on NPL performance of banking, If the implementation of ERM is good, so the performance of NPL will also better. This study investigate the effect of ERM implementation on NPL performance on islamic banking and conventional banking. This study also investigate a different test level of ERM implementation that affect NPL on each type of banking. The sample consisted of 30 conventional banks listed on the Indonesia Stock Exchange and 10 Islamic banking based on the Islamic Banking Statistics that issued by Bank Indonesia for the 2011-2016 research period. This study find that the implementation of ERM has a significant negative effect both on the islamic banking and on conventional banking. While the results of different tests conducted show that the implementation of ERM to NPL has more influence on conventional banking than in islamic banking, this could be due to the maturity level of both types of banks. Conventional banking has also existed for a long time compared to Islamic, so it certainly has a functioning structure efficiently, but for Islamic banking still requires effort and improvement for further development.